The Effect of Nutritional Counseling using Online Media (Nutrilove) on The Nutritional Knowledge of Pregnant Women - Bunga Putri Arindra; Bastianus Doddy Riyadi; Juin Hadisuyitno; Sugeng Iwan Setyobudi (Universitas Airlangga, 2024)
Anemia in pregnant women is a nutritional problem that has not yet been solved. The cause of anemia is directly due to the unavailability of sufficient nutrients in the body and indirectly caused by a lack of knowledge of pregnant women. This study aimed to determine the difference in the knowledge of pregnant women with lecture method counseling using the educational media Nutrilove website. This type of research is a quasi-experimental non-randomized control group pre-test post-test design. The sample consisted of 24 pregnant women in Wandanpuro Bululawang Village who were divided into 2 groups, the control group consisted of 12 pregnant women who were not given any intervention and the intervention group consisted of 12 people who were given lectures using the Nutrilove website media. The knowledge score was carried out 2 times, before and 3 weeks after the intervention and grouped into 3 categories, good, sufficient, and poor. Statistical tests used paired sample t-test and independent t-test. There was a significant difference in knowledge before and after intervention (p=0.005) and a significant difference in the knowledge of pregnant women between the control group and the treatment group (p=0.001). The counseling method using the Nutrilove website media can increase pregnant women's knowledge about the importance of consuming iron and folic acid in preventing anemia.